CONSTRUCTING KURDISH NATIONALIST IDENTITY THROUGH LYRICAL NARRATIVES IN POPULAR MUSIC - Rasim Özgür DÖNMEZ (Alternatif Politika)
This paper analyses how Kurdish ethno-nationalism and nationalist identity have been predominantly promoted through the lyrics of popular Kurdish music, with performance, sounds and rhythms as strong support for lyrical narratives depicting Kurdish nationalism. The analysis of the lyrics is to evaluate the subject from a political science perspective, which limited the author’s methodological analysis of sounds, rhythms and performances which music anthropologists or cultural studies students often utilize. In this study, the author argues that Kurdish popular music is both constitutive and represents social positioning, in the form of Kurdish nationalism. Music is thus perceived as a means and a representation of the imaginary Kurdish nation and Kurdish popular music is a form of cultural resistance for Kurds, against Turkish state policies. This investigation firstly examines traditional and popular Kurdish music, evaluates such music in Turkey and the relationship between Kurds and the Turkish state. Secondly, musical structure in general and particularly lyrics of popular Kurdish songs, are analysed, to determine the boundaries of the Kurdish nationalist identity.